Meningkatkan Keterampilan Membaca Pada Anak Sekolah Dasar Kelas Tinggi Dengan Menggunakan Metode PQ4R (Preview, Question, Read, Reflect, Recite, Review) - Adien Inayah; Fadillah Annisak; Pramudia Ananda; Riska Rahman Tanjung; Siti Fadilla (Jurnal Bintang Pendidikan Indonesia, 2023)
This study aims to determine the effectiveness of using the PQ4R (Preview, Question, Read, Reflect, Recite, Review) method in improving reading skills in elementary school children in high grades. The research method used in this research uses qualitative methods with a literature study approach. Research with literature or literature study is a data collection technique by conducting a review of books, literature, records and various reports related to the problem to be solved to reach a conclusion. This study provides recommendations for educators and education practitioners to consider using the PQ4R (Preview, Question, Read, Reflect, Recite, Review) method to improve reading skills in high school elementary school children. Proper and integrated implementation of the use of this method can be an effective alternative in developing students reading skills and creating a more meaningful learning experience in the learning process at school. The results showed that the use of the PQ4R method (Preview, Question, Read, Reflect, Recite, Review) can significantly improve students skills in reading but there are also some drawbacks when using the PQ4R method (Preview, Question, Read, Reflect, Recite, Review). This method relies on the performance of the brain's memory so that it can improve student understanding, because at this stage of the method carrying out reading activities repeatedly, the information obtained will stick in the students memory longer. While this method is not effective in a small amount of time because this method requires a lot of time, especially at the read stage.